2020
DOI: 10.22219/kinetik.v5i2.1037
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Metasploit Attacks Using RAM Forensic on Proprietary Operating Systems

Abstract: Information technology has become an essential thing in the digital era as it is today. With the support of computer networks, information technology is used as a medium for exchanging data and information. Much information is confidential. Therefore, security is also essential. Metasploit is one of the frameworks commonly used by penetration testers to audit or test the security of a computer system legally, but it does not rule out the possibility that Metasploit can also be used for crime. For this reason, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Arfeen et al [6] developed a framework for memory acquisition periodically to analyze process behavior while it is running and reside in memory to help ransomware detection. Prakoso et al [7] examined how Metasploit attacks on Windows 10 can be analyzed using live forensics techniques on the volatile memory. The study used three well-known RAM acquisition tools, namely: FTK Imager, Dumpit, and Magnet RAM Capture.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Arfeen et al [6] developed a framework for memory acquisition periodically to analyze process behavior while it is running and reside in memory to help ransomware detection. Prakoso et al [7] examined how Metasploit attacks on Windows 10 can be analyzed using live forensics techniques on the volatile memory. The study used three well-known RAM acquisition tools, namely: FTK Imager, Dumpit, and Magnet RAM Capture.…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, [14] also examined how the combination of Belkasoft RAM Capturer, FTK Imager, and Winhex can be utilized to obtain data for the Line app in Windows 8.1. Prakoso et al [7] identified that FTK Imager, Dumpit, and Magnet RAM Capture, have the same performance in acquiring the targeted artifact of a Metasploit attack in Windows 10 based on their acquisition results comparison.…”
Section: Related Workmentioning
confidence: 99%
“…Much of the data is confidential. Therefore, safety is likewise essential [18,19]. This allows you to properly protect your sensitive data and protect it from the various negative effects of cyberattacks.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of information is confidential. Therefore, security is also essential [22] [23]. As a result, sensitive data can be properly maintained and protected from various bad effects of cyber attacks.…”
Section: Introductionmentioning
confidence: 99%